ChemInform Abstract: Model Foldamers: Applications and Structures of Stable Macrocyclic Peptides Identified Using in vitro Selection. Issue 28 (July 2015) - Jongkees, Seino A. K.; Hipolito, Christopher J.; Rogers, Joseph M.; Suga, Hiroaki
Abstract Review: 46 refs.